ANALYSIS OF THE DIFFERENCES IN CONSUMER PREFERENCES TOWARDS PURCHASING LOCAL ORANGES AND IMPORTED ORANGES IN THE MODERN MARKET OF MEDAN CITY - Nona Valentine Sirait; Salmiah; Lindawati (CV. Radja Publika, 2024)
This research is motivated by the fact that citrus fruit is a fruit that is widely consumed and has high demand. Increasing consumer demand for citrus fruit cannot be avoided. The more imported citrus products on the national market, the more competition there will be between local citrus fruit and imported citrus fruit. Imported orange fruit is often found in various cities and districts in Indonesia, including Medan City, therefore this research is needed to determine the characteristics and behavior and preferences of consumers towards local and imported orange fruit in the Medan City Modern Market. This research aims to examine what attributes consumers prefer when buying local and imported oranges at the Medan City Modern Market and analyze which attributes consumers most consider when buying local and imported oranges at the Medan City Modern Market. The data used is primary data. The data analysis used was Chi-Square and Multiattribute Fishbein. The results of the research show that there are differences in consumer preferences for the attributes of local oranges and imported oranges, except for the taste attribute. The local orange fruit that is the preference of consumers at the Medan City Modern Market is that it has a sweet taste, the price of oranges is <Rp. 20,000/Kg, the orange packaging is not wrapped, the benefits of oranges as an embodiment of a healthy lifestyle, the skin color is greenish yellow, the skin texture is smooth with large pores , durability at room temperature, large variety of fruit, direct promotion on location, ease of obtaining based on stock availability, number of seeds 1-3 seeds, high water content, yellow-orange flesh color. Meanwhile, the preference for imported oranges is that they have a sweet taste, the price of oranges is IDR 30,001–IDR 40,000/Kg, the orange packaging is wrapped in plastic, the benefits of oranges are to fulfill nutritional needs, the color of the skin is orange-yellow, the texture of the skin is smooth with small pores, the resistance to temperature cooler, medium sized variety, direct promotion on location, ease of obtaining based on stock availability, no number of seeds, high water content, and orange flesh color.